Association between inflammatory burden index and risk of heart failure: evidence from NHANES 2003–2017 - Li-Xin Yun; Wan-Zhong Huang; Changjing He; Yuan Huang; Hua-Feng Yang; Qiang Su; Da-Zhi Lan; Yang-Chun Liu (BMC Cardiovascular Disorders)
Abstract Background Systemic inflammation contributes to the progression of heart failure (HF). This study aims to investigate the association between inflammatory burden index (IBI) and HF risk. Methods In this cross-sectional study of NHANES 2003–2017, data from 19,856 participants were analyzed, including 652 participants with HF and 19,204 without HF. Participants were categorized into quartiles based on IBI levels (Q1–Q4). The risk of HF across these quartiles was assessed with adjustment for potential confounders and restricted cubic spline analyses were used to evaluate dose-response relationships. Results Our results show that participants with HF have higher IBI levels compared to those without HF (2.66 ± 0.27 vs. 1.05 ± 0.03, p < 0.001). The prevalence of HF increases with higher IBI quartiles: Quartile 1 (1.2%), Quartile 2 (1.33%), Quartile 3 (2.60%), and Quartile 4 (4.37%) (p < 0.001). After adjusting for potential confounders, the risk of HF remained elevated across the quartiles: Quartile 2 (odds ratio [OR] = 0.72, 95% confidence interval [CI]: 0.48–1.10), Quartile 3 (OR = 1.06, 95% CI: 0.70–1.61), and Quartile 4 (OR = 1.46, 95% CI: 1.02–2.10) compared to Quartile 1. Restricted cubic spline analysis further confirmed a substantial positive-linear correlation between IBI and HF risk. Conclusion Higher levels of IBI are related to a high risk of HF, independent of traditional risk factors. These results suggest that IBI could be a useful parameter for identifying individuals at higher risk of HF. Clinical trial number Not applicable.